2017
DOI: 10.1136/bcr-2017-220654
|View full text |Cite
|
Sign up to set email alerts
|

Bacteraemia and liver abscess due toFusobacterium necrophorum

Abstract: is the oropharyngeal pathogen usually associated with Lemierre's syndrome, a pharyngeal infection which evolves to sepsis, septic emboli and thrombophlebitis of the adjacent neck vessels. It is an uncommon causative bacteria of a liver abscess, and an extensive workup should, therefore, be performed in order to rule out potential sources of the infection. This case report describes the workup that led to the diagnosis of a colorectal carcinoma, which was deemed to be the source of the bacteraemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…We treated the patient with IV piperacillin-tazobactam as empiric treatment for a pyogenic liver abscess16 for 4 weeks followed by a 2-week oral tail of amoxicillin-clavulanic acid which resulted in complete clinical, biochemical and radiological recovery. While previous evidence has suggested that F. necrophorum has a high likelihood of resistance to aminoglycosides, tetracyclines, macrolides and fluoroquinolones,17 various regimens have been successfully used to treat infection including cephalosporins, metronidazole and carbapenems 12 18 19. Generally, 4–6 weeks of antibiotic therapy is sufficient in patients who respond well to abscess drainage12 20 as was the case in our patient.…”
Section: Discussionmentioning
confidence: 52%
“…We treated the patient with IV piperacillin-tazobactam as empiric treatment for a pyogenic liver abscess16 for 4 weeks followed by a 2-week oral tail of amoxicillin-clavulanic acid which resulted in complete clinical, biochemical and radiological recovery. While previous evidence has suggested that F. necrophorum has a high likelihood of resistance to aminoglycosides, tetracyclines, macrolides and fluoroquinolones,17 various regimens have been successfully used to treat infection including cephalosporins, metronidazole and carbapenems 12 18 19. Generally, 4–6 weeks of antibiotic therapy is sufficient in patients who respond well to abscess drainage12 20 as was the case in our patient.…”
Section: Discussionmentioning
confidence: 52%
“…Another case of Fusobacterium septicemia and liver abscess was recently reported in which the source was found to be colorectal cancer 4. Recent literature has also shown an increased risk of colorectal cancer in patients with bacteremia from Fusobacterium nucleatum 12…”
Section: Discussionmentioning
confidence: 99%
“…It is known to cause Lemierre’s syndrome, which is characterized by an oropharyngeal infection followed by septic thrombophlebitis of the internal jugular vein with embolization to different organs, including lungs and liver 2. Although Fusobacterium infection originating in the GI tract is rare and seldom reported, it can invade the GI mucosa and cause bacteremia with fatal complications 3-5…”
Section: Introductionmentioning
confidence: 99%
“…In our patient, two Gram-negative species were able to be isolated ( Klebsiella and Fusobacterium ). Some publications have reported liver abscesses associated with periodontal diseases7 and intestinal malignancy 8 9. The main risk factor for liver abscesses is hepatobiliary or colorectal disease, whether malignancies or infections.…”
Section: Discussionmentioning
confidence: 99%